Revisiting the role of pathogen diversity and microbial interactions in honeybee susceptibility and treatment of Melissococcus plutonius infection - Mallory, Elizabeth; Freeze, Gwendolyn; Daisley, Brendan A.; Allen-Vercoe, Emma (Frontiers in Veterinary Science, 2024)
European Foulbrood (EFB) is a severe bacterial disease affecting honeybees, primarily caused by the Gram-positive bacterium Melissococcus plutonius. Although the presence of M. plutonius is associated with EFB, it does not consistently predict the manifestation of symptoms, and the role of ‘secondary invaders’ in the disease’s development remains a subject of ongoing debate. This review provides an updated synthesis of the microbial ecological factors that influence the expression of EFB symptoms, which have often been overlooked in previous research. In addition, this review examines the potential negative health consequences of prolonged antibiotic use in bee colonies for treating EFB, and proposes innovative and sustainable alternatives. These include the development of probiotics and targeted microbiota management techniques, aiming to enhance the overall resilience of bee populations to this debilitating disease.